PERAN GURU DALAM MENUMBUHKAN SIKAP TOLERANSI BERAGAMA DI SMP NEGERI 3 BANJARMASIN - Muhammad Luthfi Ansari; Muhammad Elmy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Cultivating an attitude of religious tolerance is a crucial issue in the context of Indonesia’s diverse society. Given students’ diverse beliefs, the value of tolerance needs to be strengthened to foster harmony and prevent primordial conflict in the school environment. SMP Negeri 3 Banjarmasin is a strategic institution in implementing these values because schools are the primary place for character formation and religious moderation for the younger generation. This study aims to analyze three indicators of the implementation of the teacher’s role, namely: planning, implementation, and evaluation, in cultivating an attitude of religious tolerance, so that a method is needed that can in-depth explore information from data sources, such as qualitative methods. It is preceded by field reality observations, followed by interviews to dig deeper into information, and documenting supporting documents. The data is then analyzed through the stages of eliminating data that does not answer the formulation, then presenting it systematically for easy understanding, and drawing conclusions that answer the formulation. As a result, a plan to cultivate an attitude of tolerance in students is formulated by teachers through the integration of tolerance values into learning tools (RPP/Teaching Modules), the preparation of inclusive school regulations, and the planning of interfaith programs in schools.  The role of teachers is realized through exemplary methods, interactive dialogue in Pancasila and Citizenship Education (PPKn) and Religion lessons, and facilitation of student activities that uphold diversity. Evaluation is carried out through consistent monitoring of changes in student behavior, assessment of social attitudes, and the sustainability of a school culture that creates a safe atmosphere for all religious adherents. Therefore, the role of teachers at SMP Negeri 3 Banjarmasin is very significant in developing students’ religious tolerance.